Earthworm-Collembola interactions affecting water-soluble nutrients, fauna and physiochemistry in a mesocosm manure-straw composting experiment. (October 2021) - Jacques, R.G.; Allison, G.; Shaw, P.; Griffith, G.W.; Scullion, J.
Highlights: Earthworms accelerated compost mineralisation and changes in composition (NIRS). Earthworms increased Collembola abundance overall but species responses differed. Collembola alone affected compost composition but nutrients only after 136 days. Earthworm effects were mitigated by Collembola early in the composting process. Collembola effects were more pronounced later as earthworm abundance declined. Abstract: A mesocosm fermentation experiment was undertaken to investigate interactions between Eisenia fetida and Collembola affecting composting processes. Earthworms, Collembola, respiration, water soluble nutrients and compost characteristics (near infrared spectra – NIRS) were monitored on four occasions over 136 days. Earthworms were the main drivers of early changes in composts, increasing the general abundance of Collembola, although responses varied with species. Earthworms accelerated substrate mineralisation and release of soluble nutrients whilst also changing compost characteristics. Collembola alone had little direct effect on soluble nutrient concentrations or respiration; they did however alter compost characteristics (NIR spectra). Earthworm-Collembola interactions affecting respiration and soluble nutrients were mainly antagonistic in the early stages of composting but synergistic in later stages. In the later stages of composting, the higher abundance of Collembola when combined with earthworms resulted in greater concentrations of soluble nitrate and phosphate. These findings emphasise the importance in vermicomposting practice of different invertebrate groups having access to feedstock at appropriate stages of the process. The high concentrations of soluble nutrients released during vermicomposting indicate the need for control measures to avoid off-site pollution and loss of this resource.